ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEPUNG TERIGU TERHADAP PROSES PRODUKSI ROTI DI BORNEO KUANINO KUPANG - Dhoka, Libertina; Fanggidae, Ronald P.C.; Amtiran, Paulina Y. (Universitas Nusa Cendana, 2021)
The objective of this research is finding the comparison on the raw material stock in Borneo Company by using Economic Order Quantity (EOQ) as the method. The data analysis that been used in this research is Economic Order Quantity (EOQ), the analysis determine the schedule to re-order point and deciding quantity that should be ordered by the company. According to the research’s results which had been conducted in Borneo, The author summarize that Borneo incapable to optimize the calculation toward the raw materials purchased, which the total purchased in Borneo was higher compared to the utilization of the raw materials. As a result this condition lead to the dissipation on total inventory cost. Keywords : Economic Order Quantity (EOQ), Total Inventory Cost (TIC),Safety Stock, and Re-Order Point (ROP)